P‐10: Excellent Mechanical Bending Stability of Flexible a‐IGZO TFT by Dual Gate Dual Sweep Using TCAD Simulation. Issue 1 (May 2016) - Billah, Mohammad Masum; Hasan, Md Mehedi; Chowdhury, Md Delwar Hossain; Jang, Jin
Abstract : We report mechanical bending effect on electrical performance of flexible amorphous‐indium‐gallium‐zinc‐oxide (a‐IGZO) thin film transistors (TFTs) using TCAD simulation. Tensile bending stress for a single gate (SG) TFT exhibits higher electron concentration and lower resistivity along the channel than those of flat and compressive geometries. The dual gate (DG) TFT with dual gate sweep (DS) shows increased conductivity and improved bending stability. These findings are an important step toward the realization of high performance DG flexible TFTs for future display applications.